Pengaruh Kualitas Produk, Persepsi Harga Dan Citra Merek Terhadap Keputusan Pembelian Di Steak 21 Mall Kota Kasablanka - Alfian, Candra; MH Nainggolan, Bonifasius (CV. Lafadz Jaya, 2022)
This study intends to examine the effect of product quality, price perception, and brand image on purchasing decisions. Testing this hypothesis using multiple linear regression analysis testing methods and the help of SPSS software version 20. The survey was carried out from April to June 22 located at Steak 21 outlets Kota Kasablanka mall by distributing questionnaires to Steak 21 buyers as many as 120 respondents, of which 20 respondents be the sample and 100 respondents are the data. The results of this study indicate that product quality gets a significant value of 0.001, price perception gets a significant value of 0.001 and brand image gets a significant value of 0.000. So product quality, price perception and brand image have a positive and significant impact on purchasing decisions at Steak 21 Kota Kasablanka Mall.